Comparison of two antifungal susceptibility testing of Candida sp. isolates using agar diffusion method: Neo-sensitabs® tablets and Bio-rad® disks - UWINGABIYE, JEAN; IKEN, MERYEM; ZOHOUN, ALBAN GILDAS COMLAN; BOUMHIL, LAILA; LEMKHENTE, ZOHRA; NAOUI, HAFIDA; BOUCHRICK, MOURAD; LMIMOUNI, BADRE EDDINE (My University, 2016)
Introduction The aim of our study was to evaluate the concordance between the two antifungal susceptibility testing of Candida sp. isolates using agar diffusion method: Neo-Sensitabs® tablets and Bio-Rad® disks. Materials and methods This is a prospective study conducted in the Laboratory of Parasitology and Mycology of the Mohammed V military teaching hospital from February to August 2012. Upon receiving blood cultures and peripheral sites samples, the identification of Candida isolates performed using routine phenotypic standard tests and the realization of the antifungal susceptibility was carried out on Neo-sensitabs® tablets and Bio-Rad® disks. Results A total of 38 Candida strains were isolated: 15 C. albicans (39%), 13 C. glabrata (34%), 5 C. tropicalis (13%), 4 C. krusei (11%) and 1 C. dubliniensis (3%). There were no significant difference (P > 0.05) in susceptibility rate between both methods for all antifungal agents tested except for 5-fluorocytosine. The concordance percentage between two methods was 100% for amphotericin B, 97.4% for fluconazole, 94.7% for voriconazole and 73% for 5-fluorocytosine. Conclusion Both methods are easy to perform, rapid and cost effective. Our results showed the best agreement between the two methods for testing the susceptibility of Candida isolates to amphotericin B, fluconazole and voriconazole while for the 5-fluorocytosine, the concordance rate was low.
Keywords: Antifungal susceptibility methods; Agar diffusion method; Concordance; Candida; Antifungal agents